Multifunkcionalnost v oblikovanju: Zbrano gradivo - Šterman, Sonja; Stjepanović, Zoran (University of Maribor Press, 2020)
Multifunctionality in Design: Collected Material.The collected material for the object Multifunctionality in design provides basic knowledge of multifunctionality in design. The first chapter covers the field of multifunctionality in various contexts that affect quality of life, adapt to ecological standards and individual needs, and interact with new media and technologies. The second section highlights examples of multifunctionality in the design of useful and technical products that are already recognized and widely used, or hardly rewarded examples of multifunctional solutions that promise future use. The chapter also covers multifunctionality and new technologies, as well as examples in the field of textile design, apparel and accessories, which, with advanced technologies, gain important dimensions of modern products. The third chapter highlights creative processes for creative idea generation, which, through different approaches and transferable forms and functions, create new creative solutions. Examples are presented in the context of the tasks given that helps by development of creativity.